Banking and Leverage: Toward a Model of Financial Stability - Issa, Samar; Issa, Hussein (Journal of Applied Business and Economics, 2020)
This paper presents a theoretical model of bank leveraging based on Stein (2011, 2012) and Brunnermeier and Sannikov (2014). The paper offers an analytical review of the literature on bank leveraging and focuses on the adverse effects of excessive leverage and the vulnerabilities and credit contractions that can subsequently occur. Moreover, this paper solves the optimal control problem of the model with a finite time decision horizon to present an analysis of the dynamics of net worth and optimal or sustainable leverage, including a discussion of periods of high and low interest rates. The study shows that overleveraging and optimal debt move in opposite directions. Furthermore, a literature review on bank leverage and monetary policy is presented followed by an analysis of the link between credit growth, GDP growth, and overleveraging in five countries. The findings show that periods of low credit growth are accompanied by periods of low GDP growth because constrained credit limits investments as well as consumption in many cases.